Extra credit - Clements, Andrew, 1949-; Elliott, Mark, 1967- (New York : Atheneum Books for Young Readers, 2009)
As letters flow back and forth--between the prairies of Illinois and the mountains of Afghanistan, across cultural and religious divides--sixth-grader Abby, ten-year-old Amira, and eleven-year-old Sadeed begin to speak and listen to each other
Grades 4-6
830
Keywords: Letters -- Juvenile fiction; Pen pals -- Juvenile fiction; Family -- Afghanistan -- Juvenile fiction; Family -- Illinois -- Juvenile fiction